Generation of Influenza A Virus NS2 (NEP) Mutants with an Altered Nuclear Export Signal Sequence - Iwatsuki-Horimoto, Kiyoko (American Society for Microbiology, 2004)
The NS2 (NEP) protein of influenza A virus contains a highly conserved nuclear export signal (NES) motif in its amino-terminal region ((12)ILMRMSKMQL(21), A/WSN/33), which is thought to be required for nuclear export of viral ribonucleoprotein complexes (vRNPs) mediated by a cellular export factor, CRM1. However, simultaneous replacement of three hydrophobic residues in the NES with alanine does not affect NS2 (NEP) binding to CRM1, although the virus with these mutations is not viable. To determine the extent of sequence conservation required by the NS2 (NEP) NES for its export function during viral replication, we randomly introduced mutations by degenerative mutagenesis into the region of NS cDNA encoding the NS2 (NEP) NES and then attempted to generate mutant viruses containing these alterations by reverse genetics. Sequence analysis of the recovered viruses showed that although some of the mutants possessed amino acids other than those conserved in the NES, hydrophobicity within this motif was maintained. Nuclear export of vRNPs representing all of the mutant viruses was completely inhibited in the presence of a CRM1 inhibitor, leptomycin B, as was the transport of wild-type virus, indicating that the CRM1-mediated pathway is responsible for the nuclear export of both wild-type and mutant vRNPs. The vRNPs of some of the mutant viruses were exported in a delayed manner, resulting in limited viral growth in cell culture and in mice. These results suggest that the NES motif may be an attractive target for the introduction of attenuating mutations in the production of live vaccine viruses.